2023
DOI: 10.2147/ccid.s413237
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Mutual Promotion of Rosacea, Anxiety, and Depression from Neuroendocrine Immune Aspects

Abstract: Rosacea is a common chronic inflammatory skin disease with a complex etiology and undefined pathogenesis, and there is still a lack of targeted clinical treatment. Patients with rosacea are at a higher risk of anxiety and depression compared to the healthy population. Compared to skin conditions such as acne and psoriasis, rosacea has been much less studied in relation to multiple-etiology psychiatric disorders such as anxiety and depression. In contrast to the mainstream belief that the causal association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In the current study, it was found that a majority of patients with headaches developed their headaches after being diagnosed with rosacea. A shared vascular change between rosacea and certain headache types, along with neurogenic modulation, might play a role [ 21 , 22 ]. The variability in headache types among different rosacea predominant subtypes further suggests a complex interplay, where specific inflammatory and pathophysiological features of each subtype differentially impact neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, it was found that a majority of patients with headaches developed their headaches after being diagnosed with rosacea. A shared vascular change between rosacea and certain headache types, along with neurogenic modulation, might play a role [ 21 , 22 ]. The variability in headache types among different rosacea predominant subtypes further suggests a complex interplay, where specific inflammatory and pathophysiological features of each subtype differentially impact neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect is the influence of cannabinoids, plant or synthetic compounds, which interact with cannabinoid receptors in the skin to regulate neuroendocrine processes. Cannabinoid receptors, mainly CB 1 and CB 2 , present in skin cells and the nervous system, form the foundations of the interaction between the endocannabinoid system and skin neuroendocrinology [ 29 , 30 , 31 ]. In the context of neuroendocrinology, cannabinoids can influence hormone secretion by interacting with cell receptors or indirectly, by influencing stress responses.…”
Section: Mechanisms Of Action Of Cannabinoids On the Skin And Their I...mentioning
confidence: 99%
“…Environmental factors such as UV radiation and pollutants expedite this process, disrupting cutaneous neuroendocrine systems. Topical application of neurohormonal substances, like melatonin, secosteroids and cannabinoids may mitigate skin aging effects through targeted interaction with receptors and enzymes [ 26 , 27 , 28 , 29 ].…”
Section: Mechanisms Of Action Of Cannabinoids On the Skin And Their I...mentioning
confidence: 99%